Report on Candidates' Work in the Secondary Education Certificate General and Basic Proficiency Examinations June 1989: Social Studies - Caribbean Examinations Council (CXC, 1989)
This report contains general and specific comments on the performance of candidates in the June 1989 Caribbean Secondary Education Certificate (CSEC) general and basic proficiency examinations in Social Studies.
Keywords: CXC CSEC examinations